Effects of Dextrose and Lipopolysaccharide on the Corrosion Behavior of a Ti-6Al-4V Alloy with a Smooth Surface or Treated with Double-Acid-Etching - Faverani, Leonardo P. [UNESP]; Assunção, Wirley Goncalves [UNESP]; Carvalho, Paulo Sergio P. de [UNESP]; Yuan, Judy Chia-Chun; Sukotjo, Cortino; Mathew, Mathew T.; Barao, Valentim A. (Public Library Science, 2014)
Diabetes and infections are associated with a high risk of implant failure. However, the effects of such conditions on the electrochemical stability of titanium materials remain unclear. This study evaluated the corrosion behavior of a Ti-6Al-4V alloy, with a smooth surface or conditioned by double-acid-etching, in simulated body fluid with different concentrations of dextrose and lipopolysaccharide. For the electrochemical assay, the open-circuit-potential, electrochemical impedance spectroscopy, and potentiodynamic test were used. The disc surfaces were characterized by scanning electron microscopy and atomic force microscopy. Their surface roughness and Vickers microhardness were also tested. The quantitative data were analyzed by Pearson's correlation and independent t-tests (alpha = 0.05). In the corrosion parameters, there was a strong lipopolysaccharide correlation with the I-pass (passivation current density), C-dl (double-layer capacitance), and R-p (polarization resistance) values (p<0.05) for the Ti-6Al-4V alloy with surface treatment by double-acid-etching. The combination of dextrose and lipopolysaccharide was correlated with the I-corr (corrosion current density) and I-pass (p<0.05). The acid-treated groups showed a significant increase in C-dl values and reduced R-p values (p<0.05, t-test). According to the topography, there was an increase in surface roughness (R-2 = 0.726, p<0.0001 for the smooth surface; R-2 = 0.405, p = 0.036 for the double-acid-etching-treated surface). The microhardness of the smooth Ti-6Al-4V alloy decreased (p<0.05) and that of the treated Ti-6Al-4V alloy increased (p<0.0001). Atomic force microscopy showed changes in the microstructure of the Ti-6Al-4V alloy by increasing the surface thickness mainly in the group associated with dextrose and lipopolysaccharide. The combination of dextrose and lipopolysaccharide affected the corrosion behavior of the Ti-6Al-4V alloy surface treated with double-acid-etching. However, no dose-response corrosion behavior could be observed. These results suggest a greater susceptibility to corrosion of titanium implants in diabetic patients with associated infections.